A COMPARATIVE STUDY OF ADOLESCENT REALITIES AND FEMALE AGENCY: HADINELENTU AND ALL WE IMAGINE TO BE LIGHT - Chandan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article presents a comparative study of the Kannada film Hadinelentu (Seventeeners) and the Hindi film All We Imagine to Be Light, both of which delve into the complexities of gender, caste, and societal norms. While Hadinelentu focuses on the repercussions of adolescent sexual exploration in a caste-conscious society, All We Imagine to Be Light portrays the intersecting lives of three women grappling with personal and societal expectations. By examining the films’ thematic elements, narrative structures, and socio-cultural implications, this study sheds light on their representation of contemporary issues and their contributions to progressive cinematic discourse.